PENGEMBANGAN KURIKULUM PROGRAM STUDI BAHASA DAN SASTRA INGGRIS FAKULTAS ILMU BUDAYA UNIVERSITAS DIPONEGORO - Widodo Agus Syahrir Syam (PAROLE: Journal of Linguistics and Education, 2011)
This article deals with the curriculum development at the English department, faculty of cultural science, Diponegoro university. Some concepts of curriculum ideology and curriculum models are presented with the purpose to serve as a basis in developing curriculum at the English department. It is suggested that a systematic approach to curriculum design involving a core design and institutional curriculum be adopted at the English department.   Keywords    :    Curriculum ideology, model of rational curriculum, model of systematic curriculum, core curriculum, institutional curriculum